Comparative simulation studies of multipacting in higher-order-mode couplers of superconducting rf cavities - Y. M. Li; K. X. Liu; R. L. Geng (Physical Review Special Topics. Accelerators and Beams, 2014)
Multipacting (MP) in higher-order-mode (HOM) couplers of the International Linear Collider (ILC) baseline cavity and the Continuous Electron Beam Accelerator Facility (CEBAF) 12 GeV upgrade cavity is studied by using the ACE3P suites, developed by the Advanced Computations Department at SLAC. For the ILC cavity HOM coupler, the simulation results show that resonant trajectories exist in three zones, corresponding to an accelerating gradient range of 0.6–1.6  MV/m, 21–34   MV/m, 32–35  MV/m and >40  MV/m, respectively. For the CEBAF 12 GeV upgrade cavity HOM coupler, resonant trajectories exist in one zone, corresponding to an accelerating gradient range of 6–13  MV/m. Potential implications of these MP barriers are discussed in the context of future high-energy pulsed as well as medium-energy continuous wave accelerators based on superconducting radio frequency cavities. Frequency scaling of MP’s predicted in HOM couplers of the ILC, CEBAF upgrade, Spallation Neutron Source (SNS), and Free-Electron Laser in Hamburg (FLASH) third harmonic cavity is given and found to be in good agreement with the analytical result based on the parallel plate model.